Control of Invasive Forest Species through the Creation of a Value Chain: Acacia dealbata Biomass Recovery - Nunes, Leonel (2021)
In Portugal, some species are now considered invasive by law and have proliferated inrecent years. Among these,Acacia dealbatastands out. This work investigated the behavior ofthis species, in order to characterize and evaluate its potential as raw material for biomass pelletsproduction, while controlling its proliferation. It was found thatA. dealbatahas a large capacity forraw material supply, as cutting 2 ha resulted in about 140 tons of biomass. Thus, the attributionof a market value for this material could result in a reduction in the area occupied by the invasivespecies, once the demand for it increases, causing a pressure over the resource. This pressure onthe species must be duly followed by other control measures, such as reducing the population andmitigating its proliferation. Laboratory tests have shown that both the raw material and the finishedproduct are similar to those obtained with other species normally used for biomass pellet production,such asPinus pinasterandEucalyptus globulus. Thus, it can be concluded that there is a high potentialfor this species in the production of biomass pellets for energy, and that this may be an importantcontribution to controlling the proliferation of this invasive species.